Peran Penyuluh Agama Dalam Menigkatkan Kualitas Keluarga Di Era Digital Kua Kecamatan Tamalate Kota Makassar - Hidayat J, Taufiq; Raihan, Siti; Azarina, Meisya; S, Salman; Iskandar, Muh. Irzan; Sahrial, Adi; A, Asni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The digital era is creating major transformations in many aspects of life, including family dynamics. Religious counselors play a role in guiding families to maintain quality amidst the various challenges caused by digitalization. The aim of this research is to examine the role of religious counselors in improving family standards in the digital age, with an emphasis on efficient and appropriate counseling strategies. The method used in this research involves literature study and qualitative analysis from a number of relevant sources. The findings of this research emphasize that religious counselors must master digital technology in order to spread religious messages and family advice well. In addition, they also need to function as a bridge between families and technology, and provide education about the wise and responsible use of technology. In this way, religious counselors can contribute to helping families develop resilience in the digital era.